Digestive hemorrhage due to chronic gastroduodenal ulcus - di Leoni, Francisco; Leoni, Carlos; Perdomo, Roberto (Cirugía del Uruguay, 1975)
Fifty cases of bleeding due to chronic gastroduodenal ulcer (26 duodenal, 24 gastric) are discussed. 21 of these cases corresponded to severe bleeding: 14 due to gas-trie lesions and only 7 due to duodenal lesions. Over 50 % of the cases did not show prodromic symptoms, but almost always ( 44 in 50) there was a history of chronic gastroduodenal ailment. When hematemesis was the main symptom, there was a clear predominance of the gastric location. The most used hemostatic procedure was subtotal gastrectomy. Operatory mort.ality was 16 % , and 26 % for severe hemorrhages.